Lower early-stage rectal cancer surgical approaches: therapeutic options and cancer biomarker alterations - Liu, Jian; Gao, HongJian; Wang, LiHua; Yao, Yuan; Li, XingDong; Yue, Bin (Frontiers in Surgery, 2025)
BackgroundLow early-stage rectal cancer (LeREC), typically referring to pTis and pT1 tumors without nodal involvement or lymphovascular/perineural invasion and confined to the mucosa, can potentially be treated with transanal local excision techniques. While transanal endoscopic microsurgery (TEM) remains a common minimally invasive option, it is technically demanding and costly. There remains a need for safer, simpler, and more accessible alternatives.ObjectiveTo evaluate the safety and efficacy of a simplified transanal excision (sTE) combined with the Ruiyun procedure for hemorrhoids (RPH) compared to conventional TEM in the treatment of LeREC.MethodsIn this randomized, controlled study, 48 patients with LeREC located within 12 cm of the anal verge were assigned to receive either TEM (n = 20) or sTE combined with RPH (n = 28). Surgical outcomes and postoperative complications were compared. Immunohistochemical analyses of CDK2, CDK4, CDK6, FOXD1, and PAK4 were performed on primary tumor tissues to investigate potential biomarkers associated with tumor recurrence.ResultsAll patients were followed up for 12 months. The sTE + RPH group showed reduced intraoperative bleeding, lower surgical costs, and fewer complications compared to the TEM group. Expression levels of CDK2/4/6, FOXD1, and PAK4 were observed to vary between groups and were potentially associated with recurrence risk.ConclusionThe combination of sTE and RPH may offer a safe, cost-effective, and feasible alternative to TEM for treating LeREC, particularly in resource-limited settings. It facilitates wider clinical application without compromising curative efficacy.